Arctic National Wildlife Refuge (ANWR): New Directions in the 110th Congress - Corn, M. Lynne; Gelb, Bernard A.; Baldwin, Pamela (Library of Congress. Congressional Research Service., 2007)
This report gives information on The Arctic National Wildlife Refuge (ANWR), the energy resources available in the area, and major legislative issues in the 110th Congress.